Modelos hidrológicos para estimativa de vazões e impacto de mudanças na ocupação do solo sobre a disponibilidade hídrica - Diego Adania Zanoni (2023)
Changes in land use and land cover have been intensified by population growth, urbanization and agricultural activities. These changes can have a significant impact on the hydrological cycle, including variations in water availability. Changes are happening on the Brazilian agricultural frontier, this Cerrado-Amazonia ecotone has unique characteristics and is very fragile to changes in temperature and water availability. This region is undergoing the replacement of native forest areas with pasture and agriculture. Such changes are impacting the hydrological cycle of this region, which could culminate in disputes over the right to use water between the parties of interest: agriculture, energy generation and human consumption. Given this scenario, we use hydrological basin modeling tools to assess whether there are impacts of changes in forest cover, land use and occupation, on water availability. We used the SWAT and MISDc models to simulate the flow of the basin. Then, with the SWAT model, we changed land use and occupation in 6 different scenarios (3 more conservative scenarios and 3 more anthropogenic scenarios). SWAT had an acceptable performance (NSE=0.36, KGE=0.70 and Pbias=7.03), while the MISDc model had a better performance (NSE=0.81, KGE=0.75 and Pbias=-12 ,22). The flow variations for the conservative scenarios had an average flow reduction of 13.4% and for the agricultural expansion scenarios the average flow increased by 9.7%. Changes in land use and occupation impacted the flow of the basin and in scenarios of agricultural expansion, extreme events, floods and droughts, were intensified.